Beyond accessing information: Claiming to understand in child social welfare interviews. (15th November 2018) - Iversen, Clara
Abstract : The present article investigates how people manage understanding of personal experiences in an institutional setting in which shared understanding of one party's experience can become an issue at stake: social welfare interviews with child victims of abuse. New recommendations on how to respond to child interviewees limit interviewers' support to experiences of which they have direct access. Using conversation analysis and discursive psychology to examine cases in which interviewers respond to children's reports of experiences by claiming to understand, the current article shows that interviewers primarily use such claims after interviewees have indicated that the interviewer may not understand. By claiming to understand, interviewers orient to a difference between an interview requirement – not assuming they know the children's specific experiences – and their ability to interpret the children's situations. The study shows how interviewers use claims of understanding to distinguish themselves as understanding persons from their information‐eliciting approach as social welfare investigators. Findings contribute to social psychological research on how people manage challenges related to eliciting and recognizing experience in interaction. In particular, the study offers research on interviews with child victims of abuse a new angle on the tension between information elicitation and support.